Secrets And Lies - Jaishree Misra
Product Description The Secret History meets Daddy's Girls as four old schoolfriends reunite after fifteen years in this sizzling blockbuster. You can't run away from your past! Anita, Zeba, Bubbles and Sam have a friendship that spans 20 years - a friendship born out of their years at a private girls' school in Delhi in the early Nineties. Beautiful, intelligent and secretive, they were the top clique; the girls that everyone wanted to impress - until the arrival of a newcomer to the school. 15-year-old Lily D'Souza is beautiful, gifted and acerbic and instantly threatens their superiority. Now, Anita, Sam and Bubbles live in London. Bubbles is the pampered but bored wife of a billionaire, Anita is a top journalist working for the BBC, whilst Sam tries hard to be a trophy wife for her corporate lawyer husband. Zeba remained in India, and now lives a life of unimaginable luxury as the world's reigning Bollywood queen. Called back to India for a reunion by their beloved school principal Mrs Lamb, the women must confront a secret that has haunted their adult lives. Lily's body was found on the night of their school prom and, for twenty years, the open verdict has shielded the fact that they may have had a hand in her death. But as they reunite in Delhi to find out the truth about what really happened that night, will their friendship stand the strain? Or are some things better left unsaid!?